A Qualitative Study to Examine Perceptions and Barriers to Appropriate Gestational Weight Gain among Participants in the Special Supplemental Nutrition Program for Women Infants and Children Program - Loan Pham Kim; Maria Koleilat; Shannon E. Whaley (Hindawi Limited, 2016)
Women of reproductive age are particularly at risk of obesity because of excessive gestational weight gain (GWG) and postpartum weight retention, resulting in poor health outcomes for both mothers and infants. The purpose of this qualitative study was to examine perceptions and barriers to GWG among low-income women in the WIC program to inform the development of an intervention study. Eleven focus groups were conducted and stratified by ethnicity, and each group included women of varying age, parity, and prepregnancy BMI ranges. Participants reported receiving pressure from spouse and family members to "eat for two" among multiple barriers to appropriate weight gain during pregnancy. Participants were concerned about gaining too much weight but had minimal knowledge of weight gain goals during pregnancy. Receiving regular weight monitoring was reported, but participants had inconsistent discussions about weight gain with healthcare providers. Most were not aware of the IOM guidelines nor the fact that gestational weight gain goals differed by prepregnancy weight status. Results of these focus groups analyses informed the design of a pregnancy weight tracker and accompanying educational handout for use in an intervention study. These findings suggest an important opportunity for GWG education in all settings where pregnant women are seen.